2009
DOI: 10.1002/chin.200938146
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Antimicrobial Evaluation of Some Alkoxyphthalimide Derivatives of Naphthyridine.

Abstract: Fused pyridine derivatives R 0450 Synthesis and Antimicrobial Evaluation of Some Alkoxyphthalimide Derivatives of Naphthyridine. -The majority of the synthesized title compounds (IX) and (XI) show moderate to strong antimicrobial activity. -(BHAMBI, D.; SALVI, V. K.; BAPNA, A.; PEMAWAT, G.; TALESARA*, G. L.; Indian J. Chem., Sect. B: Org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Compounds having phthalimide scaffold exhibit anti-inflammatory [ 8 ], anticancer [ 9 ], antibacterial [ 10 ], HIV-1 RT [ 11 , 12 ], and HIV-1 integrase inhibitory [ 13 ] activities. An extensive perusal of literature revealed that little work has been done on phthalimides and tetrahydrophthalimide as NNRTIs.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds having phthalimide scaffold exhibit anti-inflammatory [ 8 ], anticancer [ 9 ], antibacterial [ 10 ], HIV-1 RT [ 11 , 12 ], and HIV-1 integrase inhibitory [ 13 ] activities. An extensive perusal of literature revealed that little work has been done on phthalimides and tetrahydrophthalimide as NNRTIs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many literatures have investigated the phthalimide derivatives due to their diverse range of biological activities such as antimicrobial [2][3][4][5], antiviral [6,7], anticancer [8,9], anti-inflammatory [10,11],antiepileptic [12,13], antihyperlipidimic [14,15], antihyperglycemic [16], anxiolytic [17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are used for treatment of different diseases such as infectious diseases, 1) tuberculosis, 2) AIDS, 3) tumors, 4) multiple myeloma, 5) inflammatory diseases, 6) asthma, 7) diabetes, 8) hyperlipidemia, 9) convulsion, 10) depression. 11) Recently, they are evaluated as anti-Alzheimer's agents.…”
mentioning
confidence: 99%